On the fractional-in-time Keller-Segel model via Sonine kernels - Costa, Masterson; Cuevas, Claudio; Silva, Clessius; Soto, Herme (Topological Methods in Nonlinear Analysis, 2024)
In this paper, we study the existence and asymptotic behavior to a diffusion system which is non-local in time. As consequence of our theorems we deduce new results for the fractional-in-time Keller-Segel model. Our approach is intimately related with the Sonine kernels.